2014
DOI: 10.1111/jfbc.12106
|View full text |Cite
|
Sign up to set email alerts
|

The Ethanol Precipitate of U lva rigida Protects HeLa Cells from Hydrogen Peroxide-Induced Apoptosis

Abstract: Ulva rigida exhibits antioxidant activity that protects against oxidative stress. In the present investigation, we conducted experiments in HeLa cells exposed to hydrogen peroxide (H2O2) and found that the U. rigida ethanolic precipitate inhibited H2O2 apoptosis. This precipitate prevented the H2O2 stress‐induced decline in the mitochondrial membrane potential (MMP). P21 Bax expression was decreased in H2O2‐treated cells compared with untreated cells. Conversely, p21 Bax was consistently detected in cells that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…These results indicated that the U. rigida extract was not toxic by it self and protects HeLa cells from cytotoxicity and the deleterious effect of H 2 O 2 -mediated oxidative damage. These data are in agreement with our previous study [16,22]. The high polyphenol content found in U. rigida extracts could be partly responsible for the antioxidant power reported here.…”
Section: Cytotoxicity and Cytoprotective Effectssupporting
confidence: 94%
“…These results indicated that the U. rigida extract was not toxic by it self and protects HeLa cells from cytotoxicity and the deleterious effect of H 2 O 2 -mediated oxidative damage. These data are in agreement with our previous study [16,22]. The high polyphenol content found in U. rigida extracts could be partly responsible for the antioxidant power reported here.…”
Section: Cytotoxicity and Cytoprotective Effectssupporting
confidence: 94%
“…Regarding U. rigida, previous work is done in our laboratory clearly demonstrate that this seaweeds possess a strong antioxidant power linked to the richness of its extracts in proteins, in compounds, phenolic and polysaccharides known for their remarkable antioxidant capacities [3,12]. In addition, studies carried out in the laboratory showed that extracts of the seaweeds protect the cells against apoptosis induced by oxidative stress [25]. Moreover, our study reveals that extracts from the GSSE and U. rigida are devoid of any toxicity and has a high content of proteins, lipids, minerals and vitamins that have encouraged its extensive use as a dietary supplement for humans and animals [12,26].…”
Section: Effect Of Treatments On Intracellular Mediators Of Oxidative Stressmentioning
confidence: 93%